Telaah Al-Siyasah Al-Ahkam Al-Usrah Terhadap UUP No. 1 Tahun 1974 - Putra, Abdur Rahman Adi Saputera (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2020)
Abstract Islamic law is one of the important instruments that cannot be denied its existence and validity in Indonesia, history clearly records that its emergence was not just spontaneity, but was also colored by the tidal process of political struggle between Islamic intellectuals and state elites at the time, not with the exception of Law No. 1 of 1974 concerning Marriage which in memorandum bene is also in the vortex of the transformation. Al-Siyasah Al-Ahkam Al-Usrah or Islamic family law politics, is a process of achieving the vision and aspiration to form a